AN INTEGRAL TRANSFORM TOGETHER WITH TAYLOR SERIES AND DECOMPOSITION METHOD FOR THE SOLUTION OF NONLINEAR BOUNDARY VALUE PROBLEMS OF HIGHER ORDER - Akinola, Emmanuel Idowu; Owolabi, Johnson Adekunle; Alao, Saheed; Sunday Oloruntoyin Sangoniyi, (Malaysian Journal of Science, 2023)
This work aims to determine the approximate solutions of nonlinear boundary value problems of higher order obtained through the Aboodh Transform Series Decomposition Method (ATSDM), a method designed to find the integral and the inverse transform of the problems, expand the exponential function, and simultaneously decompose the nonlinear terms. The results obtained demonstrate that ATSDM is an excellent and trusted approximate method that can be employed to obtain accurate results for any problem similar to the one presented in this work.